Exsanguinated to death by a perforated duodenal ulcer: Masquerader apprehended on autopsy - Priyanka Mishra; Nidhin Rehman; Suvradeep Mitra; Manoj G. Madakshira (Indian Journal of Pathology and Microbiology)
Gastroduodenal perforation commonly due to spontaneous perforation of a pre-existing peptic ulcer is a surgical emergency. On laparotomy, approximately 60%–70% perforations are duodenal and 15%–20% gastric. The most prevalent etiology are Helicobacter pylori infection in 65%–70% and non-steroidal anti-inflammatory drugs (NSAIDS) abuse in 30%–50% cases depending on the prevalence of H. pylori infection. We report here the autopsy findings in a 29-year-old male who collapsed suddenly in the emergency room of our hospital after a bout of massive hematemesis.